Impact of actin polymerization and filopodia formation on herpes simplex virus entry in epithelial, neuronal, and T lymphocyte cells - Sasivimolrattana, Thanayod; Bhattarakosol, Parvapan (Frontiers in Cellular and Infection Microbiology, 2023)
Herpes simplex virus type 1 (HSV-1) has been known as a common viral pathogen that can infect several parts of the body, leading to various clinical manifestations. According to this diverse manifestation, HSV-1 infection in many cell types was demonstrated. Besides the HSV-1 cell tropism, e.g., fibroblast, epithelial, mucosal cells, and neurons, HSV-1 infections can occur in human T lymphocyte cells, especially in activated T cells. In addition, several studies found that actin polymerization and filopodia formation support HSV-1 infection in diverse cell types. Hence, the goal of this review is to explore the mechanism of HSV-1 infection in various types of cells involving filopodia formation and highlight potential future directions for HSV-1 entry-related research. Moreover, this review covers several strategies for possible anti-HSV drugs focused on the entry step, offering insights into potential therapeutic interventions.